Les Filiales brejnéviennes du musée Lénine en Asie centrale : un héritage architectural ambigu - Paul Wolkenstein (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère, 2025)
This article studies the transformation of Lenin Museum subsidiaries throughout Central Asia to discuss the notion of coloniality in the context of the late Soviet period. Based on qualitative observations, interviews and archives, the aim is to contextualize an architectural history defined by specific power relations, retracing the institutions’ deconstruction after the fall of the USSR. It then highlights factors in the acceptance or rejection of a divisive architectural heritage in order to understand how these buildings reflect a form of hegemony.